Evaluation of a 2-day First Aid Course Including Basic Resuscitation With 1,268 Primary School Children Aged 6–13 Years – A Multicenter Intervention Study (International Journal of First Aid Education)
Background: In Germany, current school-based first aid training recommendations do not include children under 13 years. Our aim was therefore to evaluate a primary school-based first aid course for children aged 6–13 years. Methods: Our 2-day course (4 hours per day) for primary schools in the German rural state Brandenburg included basic elements of scene safety, compression bandages, recovery position, and resuscitation. The evaluation of specific knowledge and skills took place 1-day post-course. Results: Among the 1,268 included children (median age 9y, 49% girls) from six primary schools, 25% had previously attended first aid courses. Most children knew emergency phone number(s) pre-course. Afterward, this knowledge improved by 15% in the 6–7-year age group (reaching 80%) whereas it remained at 90% in children aged 8–13 years. After the course, about 80% of the 8–13-year-old children (40% in 6–7-year age group) answered at least one resuscitation question correctly. In the practical skill assessments, about 80% of the 8–13-year-old children (60% in the 6–7-year age group) chose a correct or almost-correct chest compression rate during resuscitation. The correct depth of compression was achieved by about 80% (10–13 years), 60% (8–9 years), and 40% (6–7 years). Three-quarters successfully put another child in the recovery position; more than two-thirds applied a compression bandage appropriately. Conclusions: A 2-day course in a primary school setting showed considerable improvement in first aid and resuscitation skills of children aged 6–13 years. Future studies should examine these effects’ sustainability and the appropriate timing for refresher courses.